Evaluation of Total Fertility Rate (TFR) North Sumatera Province, 2017 – 2019 - Muhammad Ancha Sitorus; Milna Chairunisa (Randwick International of Social Science Journal, 2020)
This study aims to look at evaluating fertility increases from factors that affect fertility. The data processed and presented in this paper constitutes RPJMN Indicator Survey and the Program Performance and Accountability Survey (SKAP) of the North Sumatra Province BKKBN from 2017 to 2019. The target population of this survey is households, women of childbearing age 15 to 49 years, families and unmarried adolescents aged 15 to 24 years in selected clusters in the province. The sampling design used was stratified multistage sampling and for the province of North Sumatra the number of selected clusters was 78 clusters spread across 33 regencies and cities. Each cluster is listed (enumerated) and 35 eligible households are selected using systematic random sampling techniques to retrieve data. The SRPJMN/ SKAP sample target in North Sumatra Province covers 2,730 households. Information on fertility rates in this survey is based on the number of births collected from all women aged 15-49 years. The results are the increase of number TFR until 20.3% in three years, the number of ASFR also increase every year. Namely first married in the age range of 15-17 years (60%) in three years. And it also find the number of using contraception In the last 3 years (2017 - 2019) for the Province of North Sumatra, the use of a FP method / device has increased from 49.42% in 2017 to 56.25% in 2019.